DECLINING OF RIVER TRANSPORTATION IN BANJARMASIN SOUTH KALIMANTAN AND THE PROBLEMS - Imron, Masyhuri; Sudiyono, Sudiyono (Jurnal Masyarakat dan Budaya, 2023)
As a city with many rivers, people’s lives in Banjarmasin mostly depends on rivers. Besides the social and economic functions, rivers are also used to support transportation activities. Nevertheless, despite the people’s dependence nowadays river transportation has been declined. In this regard, this paper describes the causes of declining river transportation, local government’s (Banjarmasin City Government’s) policies to revitalize the rivers and their functions. Findings show that the decline of river transportation is resulted from the development of land transportation, that has led many people switched modes of transportation. Moreover, declining of river transportation also caused by changing river conditions related with silting up and constriction. Nevertheless, river transportation is still needed by some people in the hinterland. To revive river transportation, the local government has implemented two programs, namely river-based tourism and rivers management that support the river transportation system. This paper is based on the results of qualitative research about people shipping in Banjarmasin, and data was analyzed in descriptive analysis.